Problem Solving Ability in Early Children's Mathematics Learning - Rostika Srihilmawati (International Journal of Emerging Issues in Early Childhood Education, 2022)
The problems in this study were (1) what kind of problem solving abilities the children had before the use of beams in learning mathematics in group B at Kartika Kindergarten class X-1 (2) what kind of problem solving ability of children after using bea media in mathematics learning in group B at Kartika Kindergarten class X-1 (3) Is there a difference in problem solving ability in group B at Kartika Kindergarten class X-1 before and after using beam or block media. The general objective in this study is to determine whether there is an effect after using beam media on problem-solving abilities in early childhood mathematics learning. This study used a pre-experimental method, the research subjects were group B children in Kartika Kindergarten class X-1 Bandung. As for the data to be obtained is the result of observations, interviews, documentation and tests. Researchers performed a pretest and posttest on group B to increase problem-solving abilities in early childhood mathematics learning. The results showed that there was an effect of beam media on the problem-solving ability in group B they got an average of 22.66% in the initial test while the final test were 27.26%.   Keywords: Beam or Block Media, Early Childhood Problem Solving Ability